Penerapan Teknik Self Disclosure Untuk Meningkatkan Well Being Remaja (Studi Kasus Pada Klien “A”): adolescent welfare, self disclosure technique - Dita Rianti; Suryati Suryati; Neni Noviza (Journal of Society Counseling, 2023)
The purpose of this study was to find out the description of adolescent welfare on client “A” at the Al-Amin Orphanage in Palembang using the self disclosure technique and also to find out the application of the self disclosure technique in improving the welfare of adolescents on client “A” at the Al-Amin Orphanage in Palembang. This study used a qualitative approach with a case study research method. The subject in this study is client “A”. Data collection techniques used are observation, interviews, and documentation. While the data analysis techniques used are pattern matching, explanation making, and time series analysis strategy. The result of this study indicate that prior to the application of the self disclosure technique client ‘A” experienced low well being characterized by feeling depressed with low self acceptance because they felt unable to be like other friends and felt unhappy in carrying out their daily activities days while living in the orphanage. For the result after applying the self disclosure technique the client has experienced a better change, namely becoming confident, not feeling inferior to other people, always curios and learning from what has never been done, starting to communicate and relate well with others, and starting to feel at home and feel happy living in an orpanage because they are able to adapt to an environment where previously they felt pressured and did not even feel comfortable living at the Al-Amin orphanage in PalembangThe purpose of this study was to find out the description of adolescent welfare on client “A” at the Al-Amin Orphanage in Palembang using the self disclosure technique and also to find out the application of the self disclosure technique in improving the welfare of adolescents on client “A” at the Al-Amin Orphanage in Palembang. This study used a qualitative approach with a case study research method. The subject in this study is client “A”. Data collection techniques used are observation, interviews, and documentation. While the data analysis techniques used are pattern matching, explanation making, and time series analysis strategy. The result of this study indicate that prior to the application of the self disclosure technique client ‘A” experienced low well being characterized by feeling depressed with low self acceptance because they felt unable to be like other friends and felt unhappy in carrying out their daily activities days while living in the orphanage. For the result after applying the self disclosure technique the client has experienced a better change, namely becoming confident, not feeling inferior to other people, always curios and learning from what has never been done, starting to communicate and relate well with others, and starting to feel at home and feel happy living in an orpanage because they are able to adapt to an environment where previously they felt pressured and did not even feel comfortable living at the Al-Amin orphanage in Palembang